2003
DOI: 10.1074/jbc.m210859200
|View full text |Cite
|
Sign up to set email alerts
|

The Krüppel-like Factor KLF2 Inhibits Peroxisome Proliferator-activated Receptor-γ Expression and Adipogenesis

Abstract: Obesity is an important public health problem associated with a number of disease states such as diabetes and arteriosclerosis. As such, an understanding of the mechanisms governing adipose tissue differentiation and function is of considerable importance. We recently reported that the Krü ppel-like zinc finger transcription factor KLF15 can induce adipocyte maturation and GLUT4 expression. In this study, we identify that a second family member, KLF2/Lung Krü ppel-like factor (LKLF), as a negative regulator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
191
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(211 citation statements)
references
References 32 publications
(39 reference statements)
14
191
2
Order By: Relevance
“…36 In another report, KLF9 competed with Sp1 for the BTE sequence in the cytochrome P4501A1 promoter. 34 Importantly, a previous work identified that KLF2 bound to a GC box at the proximal region of the PPARg2 promoter in preadipocytes and at the early stage of differentiation, 15 which is just the KLF9-binding site-II identified in the present experiment (Figures 4 and 5). Thus, it is reasonable to speculate that the endogenous KLF2 binds to this specific region on the PPARg2 promoter in pre-adipocytes, which made the PPARg2 promoter unavailable for the ectopic KLF9 proteins.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…36 In another report, KLF9 competed with Sp1 for the BTE sequence in the cytochrome P4501A1 promoter. 34 Importantly, a previous work identified that KLF2 bound to a GC box at the proximal region of the PPARg2 promoter in preadipocytes and at the early stage of differentiation, 15 which is just the KLF9-binding site-II identified in the present experiment (Figures 4 and 5). Thus, it is reasonable to speculate that the endogenous KLF2 binds to this specific region on the PPARg2 promoter in pre-adipocytes, which made the PPARg2 promoter unavailable for the ectopic KLF9 proteins.…”
Section: Discussionmentioning
confidence: 59%
“…14 Previous reports showed that KLF proteins had different expression patterns during adipogenesis and several KLFs had been proved to either promote or inhibit this process. [15][16][17][18][19][20][21] Krü ppel-like factor 9 (KLF9), previously designated as basic transcription element-binding protein-1 (BTEB1), was initially isolated from a rat liver cDNA library. 22 KLF9 was further identified to be important for development and other physiological functions.…”
mentioning
confidence: 99%
“…HDACs are enzymes that play an important role in the regulation of gene expression and are best known for their role in repressing gene transcription via interaction with transcriptional repressors [Ng and Bird, 2000]. Interestingly, both HDACs and transcriptional repressors have previously been implicated in the regulation of adipocyte differentiation: HDAC-1 has been shown to associate with the C/EBPa promoter and play an important role in preventing C/EBPa expression in unstimulated preadipocytes [Wiper-Bergeron et al, 2003], while a number of transcriptional repressors have been implicated in the regulation of adipogenesis via the direct inhibition of both C/EBPa and PPARg gene expression [Tong et al, 2000;Yun et al, 2002;Banerjee et al, 2003;Shi et al, 2003]. Hence, it is tempting to speculate that one potential mechanism by which the PGF2a-calcineurin signaling pathway may inhibit adipocyte differentiation is by inducing the expression and/or activity of an HDAC-associated transcriptional repressor that is either able to directly inhibit the expression of the PPARg and C/EBPa genes, or alternatively, acts indirectly, by inhibiting the expression of a gene(s) that is normally required to promote the expression of PPARg and C/ EBPa.…”
Section: Discussionmentioning
confidence: 99%
“…44 The Kruppel-like zincfinger transcription factor KLF2 is a negative regulator of adipocyte differentiation. 45 Common KLF2 polymorphisms are not associated with obesity in a population-based sample composed of 1155 French individuals. 46 Transgenic mice with adipose-tissue-specific overexpression of Wingless-type MMTV integration site family, member 10B (WNT10B) display a 50% reduction in body fat.…”
Section: Adipogenesismentioning
confidence: 97%